Code-Switching in Multilingual Classrooms: A Bridge or a Barrier to Language Proficiency? - Bardinas, Jashlyn; Campos, Shinjane; Tacang, Kimberlie; T. Minoza, Joemar (Journal of Education and Learning Environments, 2025)
This literature review examines recent studies on code-switching in multilingual classrooms and its impact on students’ language proficiency. This review analyzed 21 peer-reviewed sources from 2020 to 2025, organized chronologically and thematically. Findings show that strategic code-switching enhances engagement, comprehension, and confidence, making it a helpful scaffold in second language (L2) learning. However, excessive use may hinder language development by fostering dependency on the first language (L1), limiting L2 exposure, and increasing anxiety. While both positive and negative effects are observed, the review concludes that code-switching is most effective when used intentionally. It emphasizes the need for balanced teaching strategies and further long-term research to guide effective language instruction in multilingual settings. Future studies should monitor students’ real language skill development over time, both with and without code-switching, according to this review article. The language outcomes of children subjected to strategic code-switching versus English-only education could be compared using experimental or quasi-experimental methodologies. Similarly, a more thorough understanding of the long-term effects of code-switching can be obtained by combining test results, classroom observations, and interviews using mixed-method approaches. Additionally, case studies from different fields and grade levels can be used to ascertain how code-switching functions in a variety of learner groups and circumstances. Research could also examine educational frameworks or models to gradually reduce reliance on L1 without sacrificing comprehension or interest.